Lumbosacral disc disease in a cat - Jaeger, G. H.; Early, P. J.; Munana, K. R.; Hardie, E. M. (Veterinary and Comparative Orthopaedics and Traumatology, 2004)
An eight-year-old male castrated domestic shorthair admitted with a two-day history of acute back pain, flaccid tail, and urinary and faecal incontinence. Diagnostic tests, including myelogram, epidurogram, and CT scan revealed an extradural lesion at the L7-S1 disc space. Exploratory surgery and histopathology confirmed a Type II lumbosacral intervertebral disc protrusion. The cat regained neurological function by six weeks after surgery. This is the first case report of a cat with documented lumbosacral disc disease. Lumbosacral disease should be considered as a differential diagnosis in cats with caudal lumbar pain or neurological signs localizable to the S1-S3 spinal cord segments or peripheral nerves.
Keywords: Keywords; Cat; intervertebral disc; lumbosacral disease